(untitled) (Journal of Health Sciences, 2015)
Introduction: Progressive pseudorheumatoid dysplasia (PPD) is an autosomal recessive genetic disorder reported to be caused by gene alterations of the Wnt1-inducible signaling pathway protein 3 corresponding gene (WISP3) located on chromosome position 6q22. Up to date, there is only a handful of WISP3 mutations identified in Europe, whereas most mutations are identified in Asia and Middle East. According to our knowledge, this is the first report of genetic dissection of WISP3 associated with spondyloepiphyseal dysplasia tarda from Bosnia and Herzegovina. Based on clinical examination findings (general manifestations, physical examination, characteristics of their bones on X-ray and laboratory results), an index patient was directed to WISP3 genotyping for confirmation of suspected diagnosis of PPD.Methods: DNA was extracted from peripheral blood leukocytes. All 5 exons and their exon-intron boundaries of the WISP3 gene were amplified by polymerase chain reaction (PCR) and sequenced by Sanger method. Segregation analysis was done to confirm the familial carrier status.Results: A missense mutation (C223G) - homozygous T to G transition at c.667 in exon 4 was identified in index patient. This mutation changed codon CAG to TAG and resulted in a subsequent change of the cysteine to glycine codon. Same mutation was observed in both parents in heterozygous form confirming the familial segregation.Conclusion: Due to its nature, the identified mutation C223G in exon 4 in WISP3 gene is the most probably causative for PPD in described patient. Here we describe the PCR based method for genotyping of specific mutation in WISP3 gene. The identification of this mutation might be a valuable addition to a regional databases on rare genetic variant although a functional analysis should be performed to explain its pathological effect.